2015
DOI: 10.3389/fmars.2015.00047
|View full text |Cite
|
Sign up to set email alerts
|

First assessment of flux rates of jellyfish carcasses (jelly-falls) to the benthos reveals the importance of gelatinous material for biological C-cycling in jellyfish-dominated ecosystems

Abstract: First assessment of flux rates of jellyfish carcasses (jelly-falls) to the benthos reveals the importance of gelatinous material for biological C-cycling in jellyfish-dominated ecosystems. Front. Mar. Sci. 2:47.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 39 publications
2
40
1
Order By: Relevance
“…The jellyfish addition represented an additional C‐input of 27.4 g jelly‐C m −2 . While this jellyfish detritus input was significantly greater than previously documented for Norwegian fjords (0–13.4 mg C m −2 , Sweetman and Chapman ), it was comparatively similar to jellyfish C‐inputs documented in other areas around the world (Gulf of Oman: 1.5–75 g C m −2 , Billett et al ; Ivory Coast: 1–20 g C m −2 , Lebrato and Jones ) and therefore allowed us to relatistically measure the seafloor impact from a large pulse of gelatinous detritus. The jellyfish that were used had been collected by a Multiple Opening/Closing Net and Environmental Sensing System (MOCNESS) in Lurefjorden, western Norway, in September 2010 and immediately frozen.…”
Section: Methodssupporting
confidence: 63%
See 1 more Smart Citation
“…The jellyfish addition represented an additional C‐input of 27.4 g jelly‐C m −2 . While this jellyfish detritus input was significantly greater than previously documented for Norwegian fjords (0–13.4 mg C m −2 , Sweetman and Chapman ), it was comparatively similar to jellyfish C‐inputs documented in other areas around the world (Gulf of Oman: 1.5–75 g C m −2 , Billett et al ; Ivory Coast: 1–20 g C m −2 , Lebrato and Jones ) and therefore allowed us to relatistically measure the seafloor impact from a large pulse of gelatinous detritus. The jellyfish that were used had been collected by a Multiple Opening/Closing Net and Environmental Sensing System (MOCNESS) in Lurefjorden, western Norway, in September 2010 and immediately frozen.…”
Section: Methodssupporting
confidence: 63%
“…obs.) and deep‐sea fjords in Norway (Sweetman and Chapman ). These collective observations suggest that gelatinous zooplankton carcasses (hereafter referred to as jelly‐falls) may provide an important transport vector for organic carbon and nitrogen to the seafloor (Sweetman and Chapman ).…”
mentioning
confidence: 99%
“…Besides the high phytoplankton productivity, sediments of southern Norway fjords can be substantially enriched by nonpoint sources of terrestrial organic matter originating from fjord watersheds, as indicated by high shares of terrestrial C org estimated for Raunefjord. Additionally, in fjords in this region, massive blooms of mesopelagic medusa Periphylla periphylla can form fluxes of gelatinous C org that equal or even exceed fluxes of phytodetritus C org (Sweetman & Chapman, ). Anthropogenic pressure is obviously higher in southern Norway than in northern Norway and Arctic fjords.…”
Section: Discussionmentioning
confidence: 99%
“…When jelly‐falls accumulate at the seafloor, jelly‐falls can significantly alter marine benthic biogeochemical cycling by enhancing bacterial metabolism and reducing oxygen flux into sediments (Chelsky et al ; Sweetman et al ). The removal of carcasses by scavengers will thus play a major role in modifying the effect of jelly‐falls on the benthic environment, as well as enhancing the spatial distribution of C, N, and P transported to the deep sea by jelly‐falls (Sweetman and Chapman ; Sweetman et al ).…”
mentioning
confidence: 99%